A budget impact analysis comparing a Hydrofiber®; dressing to an alginate dressing in managing exuding venous leg ulcers in France. Issue 3 (1st October 2012) - Yan, Songkai; Colin, Xavier; Coudray‐Omnès, Carole; Guido‐Morin, Pascale; Kommala, Dheerendra R
<x xml:space="preserve">Abstract</x> An Excel model was developed to compare total costs (including primary and secondary dressings only) of Hydrofiber®; dressing (2010 branded price) versus an alginate dressing (generic or branded price) in managing exuding venous leg ulcers considering mean wear time and mean duration of exudate management phase, from the French Social Security perspective over 5 years (2011–2015). Budget impact (based on prevalence of venous leg ulcers in France) was estimated as the difference between scenario 1 (Hydrofiber®; versus alginate dressing usage proportion increasing slightly per year) and Scenario2 (proportion remaining at 2010 levels). Annual costs and net savings per patient for the dressings were calculated in analyses 1 and 2. Analysis 1 (28‐day mean exudate management phase for both Hydrofiber®; and alginate dressing groups): total costs 66·82€ Hydrofiber®;, 70·08€ generic alginate, 77·0€ branded alginate; net savings 3·26€ and 10·18€ for Hydrofiber®; versus generic and branded alginate. Analysis 2 (mean exudate management phase of 22·2 versus 28 days for Hydrofiber®; versus alginate): total costs 52·92€, 70·08€ and 77·0€, and net savings 17·10€ and 24·02€, accordingly. Total cost savings (budget impact scenario 1 minus scenario 2): Analysis 1 – 223 107€ and 696 304€ for Hydrofiber®; versus generic and branded alginate dressings, respectively; Analysis 2 – 1 169 845€ and 1 643 042€ accordingly. Sensitivity analyses indicated that results are reliable. This conservative analysis shows that effective exudate management using Hydrofiber®; dressing can produce sizeable cost savings.